Venezuelan Evangelical Digital Diaspora, Pandemics, and the Connective Power of Contemporary Worship Music - Mora, Fernando Adolfo (Religions, 2022)
During 2020-2021, the COVID-19 pandemics exacerbated the use of digital communication tools for the general population as well as for migrant and diasporic communities. Due to social distancing requirements, church activities had to be suspended or restricted, therefore, local congregations and denominations had to incorporate social media as part of their regular worship channels in an unprecedented way. At the same time, these new spaces opened an opportunity for diasporas to reconnect with their churches back home, and to participate in digital worship projects. In this paper, we study the case of the digital worship collective Adorando en Casa (AeC), which was started at the onset of the pandemics, producing several crowdsourced original musical compositions, uploaded in popular social media sites, and distributed via messaging apps. We focus on the reasons for participation of Venezuelan musicians and singers from different regions in the country, and from the large diaspora of Venezuelan Evangelicals. Additionally, we analyze the characteristics, structure, and theology of some of the songs recorded, to show how the concept of a digital diasporic spiritual consciousness is powerfully expressed through worship music.